Development of Innovative Activity and Supply Chain Strategy of Enterprises in the Age of Digital Economy - Irina Arkadevna Kodolova; Lilia MirgaziyanovnaYusupova; Tatyana ViktorovnaNikonova; Railia Rustemovna Kalimullina (International Journal of Supply Chain Management, 2019)
Abstract-The article presents the analysis of the dynamics of innovative activity and supply chain strategy of enterprises in the Republic of Tatarstan. The authors analyzed the innovative activity of enterprises and small businesses of the Republic, detailed the innovative activity of enterprises by types of economic activity, reviewed the indicators of shipped innovative goods. The article reveals the role of research and development in the activation of innovative processes and summarizes the results of innovative activity of enterprises at the regional level.